Calculated seawater d18O record of the deep thermocline (Globorotalia truncatulinoides) corrected for global ice volume from 2.5 to 1 Ma - Raddatz, Jacek; Zeeden, Christian; Kniest, Jorit; Nürnberg, Dirk (In: Raddatz, J et al. (2025): Stable oxygen isotopes of planktonic foraminifera of sediment core SO225-53-3, including calculated d18O of seawater (with and without ice volume correction) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.984802, 2025)
Measured stable oxygen isotopes measured on a surface dwelling (G.ruber) and deep dwelling foraminifera (G truncatulinoides) from a sediment core in the tropical Pacific retrieved during research cruise SO-225 to the Manihiki Plateau. Oxygen isotopes ratios of this dataset have been combined with previously published temperature reconstruction using Mg/Ca ratios (Raddatz et al. 2017, Raddatz et al 2019) to calculate the d18O of seawater through time (2.5 to 1.0 Ma) of the sea surface and deep thermocline. We also provide a surface and deep thermocline d18O-seawater record that has been correct for global ice volume using the modelled ice sheet evolution through the Quaternary by Bintanja and Van de Wal (2008).
Keywords: Manihiki Plateau; Planktonic foraminifera; West Pacific Warm Pool